DAMPAK GLOBALISASI DAN PERAN SOSOK KIYAI DI SUMENEP (Kajian Kritis Anthony Giddens pada Peran Kiyai di Sumenep, Madura) - A Zahid (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Previously, the Sumenep community defined the Islamic cleric as a sacred figure, possessing religious knowledge, and being close to the lay community. This definition agrees that the figure of him is the right choice in solving problems related to the Ummah. However, in the Sumenep community itself, such views have shifted, the figure is informed in a form that may be 360 degrees in difference, namely the political Islamic cleric. The dualism inherent is in the question, when he becomes the figure of a religious one and when he becomes a politician. The purpose of this research is to know this position in the Sumenep area, so as to avoid being biased towards the figure of the Islamic cleric. The method used in this research is descriptive qualitative with a critical approach, so that the theory and the results of the data are actually analyzed theoretically. The results of this study indicate that the position of the Islamic cleric in Sumenep experiences dualism. This happens because of the impact of globalization which changes the position from a religious figure into a politician one. So, it is not surprising if the position begins absurd and difficult to distinguish. Therefore, it effects on understanding pattern of the Sumenep community towards the Islamic cleric who has doubled positions, a religous one and a politician.